Novel interpretation strategy for searches of singly produced vectorlike quarks at the LHC - Castro, Nuno Filipe (2020)
Vectorlike quarks (VLQs) are potential signatures of physics beyond the standard model at the TeV energy scale, and major effort has been put forward at both the ATLAS and CMS experiments to search for these particles. To make these search results more relatable in the context of most plausible theories of VLQs, it is deemed important to present the analysis results in a general fashion. We investigate the challenges associated with such interpretations of singly produced VLQ searches and propose a generalized, semianalytical framework that allows for a model-independent casting of the results in terms of unconstrained free parameters of the VLQ Lagrangian. We also propose a simple parametrization of the correction factor to the single VLQ production cross section at large decay widths. We illustrate how the proposed framework can be used to conveniently represent statistical limits by numerically reinterpreting results from benchmark ATLAS and CMS analyses.